Floating pinch method for utility targeting in heat exchanger network (HEN) - Tan, Yin Ling; Ng, D.; El-Halwagi, M.; Foo, D.; Samyudia, Yudi (Elsevier, 2014)
Most of the established methods for utility targeting in a heat exchanger network (HEN) are mainly focusing on fixed stream conditions, where the flow rate, heat capacity, supply and target temperatures are fixed. However, in the process industries, the stream conditions (flow rates and temperatures) are not fixed. Therefore, the established HEN targeting methods cannot be directly applied to locate the hot and cold utility targets for HEN problem with varying flow rates and temperatures. To address this issue, a revised floating pinch method which uses binary variables to parameterise the stream locations on the composite curves, is presented in this work to identify the minimum utilities targets. The revised method simplify the earlier version of floating pinch method presented by Duran and Grossmann (1986) by avoiding the non-differentiability in the mathematical program. Two cases, one with fixed parameters while another with temperature-dependent properties and varying operating parameters are solved to illustrate the revised model.